Ability of chlorhexidine, octenidine, polyhexanide and chloroxylenol to inhibit metabolism of biofilm-forming clinical multidrug-resistant organisms. Issue 1 (January 2021) - Günther, Frank; Blessing, Brigitte; Dapunt, Ulrike; Mischnik, Alexander; Mutters, Nico T
Purpose: This in vitro study was designed to determine if standard antiseptics used for skin and environmental surface cleansing can disrupt the metabolic activity (as a measure of viability) of multidrug-resistant gram-negative bacteria, methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus isolates within their native biofilms. Methods: Sixty clinical isolates of multidrug-resistant bacteria were selected for testing in different chlorhexidine gluconate, octenidine, polyhexanide and chloroxylenol concentrations. Metabolic inhibition of biofilm for each clinical isolate was analysed using a biofilm viability assay. Results: Chlorhexidine gluconate (mean = 83.8% ± 9.8%) and octenidine (mean = 84.5% ± 6.8%) showed the greatest efficacy against biofilms of the tested microorganisms, with the greatest efficacies against MRSA. The antiseptics demonstrated the least efficacy against biofilms of Pseudomonas aeruginosa . Conclusion: Chlorhexidine gluconate and octenidine showed the greatest level of bacterial metabolic inhibition and were statistically equivalent. Polyhexanide was more effective than chloroxylenol, but both were inferior to chlorhexidine gluconate and octenidine against the tested organisms.